2016
DOI: 10.1016/j.combustflame.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of two-stage ignition in diesel engine-relevant thermochemical conditions using direct numerical simulation

Abstract: With the goal of providing a more detailed fundamental understanding of ignition processes in diesel engines, this study reports analysis of a direct numerical simulation (DNS) database. In the DNS, a pseudo turbulent mixing layer of dimethyl ether (DME) at 400 K and air at 900 K is simulated at a pressure of 40 atmospheres. At these conditions, DME exhibits a two-stage ignition and resides within the negative temperature coefficient (NTC) regime of ignition delay times, similar to diesel fuel. The analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 72 publications
1
22
0
1
Order By: Relevance
“…2(g). The cool flame can be considered as a fourth branch of the edge-flames, resembling the tetrabrachial flames as observed before under similar thermochemical conditions in the DME-air mixing layer [24,25]. The edge flames gradually collide with each other and their branches are eventually connected.…”
Section: Autoignition and Flame Developmentmentioning
confidence: 69%
See 1 more Smart Citation
“…2(g). The cool flame can be considered as a fourth branch of the edge-flames, resembling the tetrabrachial flames as observed before under similar thermochemical conditions in the DME-air mixing layer [24,25]. The edge flames gradually collide with each other and their branches are eventually connected.…”
Section: Autoignition and Flame Developmentmentioning
confidence: 69%
“…The doubly conditioned statistics revealed a two-stage autoignition. Krisman et al [24,25] recently investigated the two-stage ignition in a turbulent mixing layer of dimethyl ether (DME)-air mixture by DNS. It was found that LTC can strongly affect the timing and location of the second stage autoignition.…”
Section: Direct Numerical Simulations (Dns) Of Ignition and Flame Promentioning
confidence: 99%
“…This allowed (not shown here) to check that the imposed boundary conditions yielded satisfactory mean profiles in the area of interest where flame stabilization mechanisms were studied. Therefore, the chosen inflow boundary conditions allow to investigate the flame stabilization mechanisms, unlike temporally developing jets created by a mixing layer between fuel and air [20][21][22][23] . The initial condition for the DNS was a flow at rest at the initial temperature, pressure and composition known from the experiments.…”
Section: Numerical Set-upmentioning
confidence: 99%
“…The proportion of TF, L/R RZ is almost the same during Evolution B: 45 % TF and 55 % L/R RZ. It indicates that edge-flames must be taken into account to correctly model spray combustion under Diesel conditions as suggested in [10,17,[20][21][22][23] .…”
Section: Analysis Of Evolutions Bmentioning
confidence: 99%
See 1 more Smart Citation